SAMHD1-dependent retroviral control and escape in mice - Rehwinkel, J; Maelfait, J; Bridgeman, A; Rigby, R; Hayward, B; Liberatore, R; Bieniasz, P; Towers, G; Moita, L; Crow, Y; Bonthron, D; Reis E Sousa, C (2013)
SAMHD1 is a host restriction factor for human immunodeficiency virus 1 (HIV-1) in cultured human cells. SAMHD1 mutations cause autoimmune Aicardi-Goutières syndrome and are found in cancers including chronic lymphocytic leukaemia. SAMHD1 is a triphosphohydrolase that depletes the cellular pool of deoxynucleoside triphosphates, thereby preventing reverse transcription of retroviral genomes. However, in vivo evidence for SAMHD1's antiviral activity has been lacking. We generated Samhd1 null mice that do not develop autoimmune disease despite displaying a type I interferon signature in spleen, macrophages and fibroblasts. Samhd1-/- cells have elevated deoxynucleoside triphosphate (dNTP) levels but, surprisingly, SAMHD1 deficiency did not lead to increased infection with VSV-G-pseudotyped HIV-1 vectors. The lack of restriction is likely attributable to the fact that dNTP concentrations in SAMHD1-sufficient mouse cells are higher than the K M of HIV-1 reverse transcriptase (RT). Consistent with this notion, an HIV-1 vector mutant bearing an RT with lower affinity for dNTPs was sensitive to SAMHD1-dependent restriction in cultured cells and in mice. This shows that SAMHD1 can restrict lentiviruses in vivo and that nucleotide starvation is an evolutionarily conserved antiviral mechanism. © 2013 European Molecular Biology Organization.